Effect of sertraline on [Ca2+]i and viability of human MG63 osteosarcoma cells. (April 2013) - Lin, Ko-Long; Chi, Chao-Chuan; Lu, Ti; Tseng, Li-Ling; Wang, Jue-Long; Lu, Yi-Chau; Jan, Chung-Ren
Abstract : The antidepressant, sertraline, has been shown to have diverse in vitro effects. This study examined whether sertraline altered [Ca 2+ ]i in MG63 human osteosarcoma cells by using fura-2 as a Ca 2+ -sensitive fluorescent dye. At 50–200 µM, sertraline induced a [Ca 2+ ]i rise in a concentration-dependent manner. Ca 2+ response was decreased by removing extracellular Ca 2+, suggesting that Ca 2+ entry and release contributed to the [Ca 2+ ]i signal. Sertraline-induced Ca 2+ entry was inhibited by nifedipine, La 3+, Gd 3+, and SK&F96365. When extracellular Ca 2+ was removed, pretreatment with the endoplasmic reticulum (ER) Ca 2+ pump inhibitor, thapsigargin, or 2, 5-di-tert-butylhydroquinone (BHQ) abolished the sertraline-evoked [Ca 2+ ]i rise. Incubation with sertraline also abolished the thapsigargin or BHQ-induced [Ca 2+ ]i rise. Inhibition of phospholipase C (PLC) with U73122 abolished the sertraline-induced [Ca 2+ ]i rise. At 20–30 µM, overnight treatment with sertraline killed cells in a concentration-dependent manner. The cytotoxic effect of sertraline was not reversed by chelating cytosolic Ca 2+ with 1, 2-bis(2-aminophenoxy)ethane-N, N, N', N'-tetraacetic acid (BAPTA). Annexin V/propidium iodide staining data demonstrate that sertraline (30 µM) evoked apoptosis. Sertraline (20 and 30 µM) also increased levels of reactive oxygen species. Together, in human osteosarcoma cells, sertraline evoked a [Ca 2+ ]i rise by inducing PLC-dependent Ca 2+ release from the ER and Ca 2+ entry by L-type Ca 2+ channels and store-operated Ca 2+ channels. Sertraline induced cell death that may involve apoptosis by mitochondrial pathways.